The student response on the use of renewable energy graphical interface simulator in learning environment - Gopabala Krishnan, Lavaniya; Albani, Aliashim; Segar, Yogesswary; Ridzuan, Abdul Rahim; Ismail, Mohd Khairi; Musa, Mohd Azlan; Gunaseelan, Khemaalatha; Subramaniam, Tamil Selvan; Ibrahim, Mohd Zamri (Frontiers in Education, 2023)
The purpose of this study is to evaluate students' responses regarding the usefulness of the graphical user interface (GUI) tool in the context of their respective learning environments. The EC-GUI helps to simplify the STEM student’s education life. The EC-GUI serves as a simulator that can assist in computing formulas, designing graphs, acting as a unit converter, and automatically deriving parameters. Furthermore, the survey, which included closed and open questions, was carried out on a selection of students majoring in STEM subjects at Universiti Malaysia Terengganu (UMT) who were enrolled in the Renewable Energy course. A total of 54 respondents participated in the survey and 90.8% of them expressed satisfaction with the EC-GUI provided. The research involved using two distinct kinds of analysis: a parametric one, such as a paired sample t-test, and a non-parametric one, such as a Wilcoxon signed-rank test. The study findings indicate that the majority of the respondents feel that the difficulty level of the subjects does not change after using EC-GUI. However, it helps simplify the learning process for students in STEM fields. The p-value of the appropriate teaching aid tool is less than 0.05, indicating that the results are significant both before and after using EC-GUI. The study suggests that a similar GUI tool could be implemented in Malaysia's teaching and learning process as it is easy to build and use.